Biodiesel-diesel (up to 45%) fuel characteristics on homogeneous charge compression ignition engine - Rahman, M. M.; Kumaran, Kadirgama; Devarajan, Ramasamy; Wan Sharuzi, Wan Harun; Rizalman, Mamat; Muhamad, Mat Noor (2018)
Biodiesels are gaining more importance as a promising alternative energy resource due to the global fossil fuel crisis and emission problems. However, it was realized that the extensive utilization of biodiesel would tax the food chain and could lead to food shortages. So, the use of a blend of biodiesel with conventional fuel was suggested to balance its usage, which could still provide a beneficial greenhouse effect. From the results of the investigation, it is reported that blends containing up to 30% biodiesel have almost the same properties as diesel. Most investigation results have shown that compared to diesel, biodiesel–diesel blend provides shorter ignition delay and a reduced heat release rate as well as a slightly higher efficiency by sacrificing a small amount of fuel. The HC, CO, and PM emissions are reduced to a great extent but the NOx emission becomes slightly higher. Biodiesels are expected to reduce the dependence on imported petroleum with the associated economic vulnerability, reduce greenhouse gas emissions and other pollutants, and revitalize the economy by increasing demand and prices for agricultural products. The objective of this study is to investigate the effect of intake temperature on combustion, performance and emissions characteristics in HCCI engine using pure n-heptane, the blends of n-heptane and ethanol fuels E15, E30 (including 15%, 30% ethanol and 85%, 70% n-heptane by vol. respectively) and the blends of n-heptane and butanol fuels Bu15, Bu30 (including 15%, 30% butanol and 85%, 70% n-heptane by vol. respectively) with the help of numerical simulation. In this study, neat diethyl ether (DEE), as well as diethyl ether and ethanol blends in different percentages by volumes such as 85% diethyl ether–15% ethanol (D85E15) and 70% diethyl ether–30% ethanol (D70E30), was used as test fuels. A zero dimensional single-zone numerical simulation with reduced fuel chemistry was developed and validated. The simulations show good agreement with the experimental data and capture important combustion phase trends as engine parameters are varied with a minimum percentage of error which is less than 6%. The simulations were run at the engine speed of 1200 rpm. The inlet air temperatures were selected as 360, 375, 390, 405 and 420 K and lambda values were taken as 1.5, 1.75, 2, 2.25 and 2.5. Simulation results show that HCCI combustion was advanced with the increase of intake temperature. Thermal efficiency was increased by about 17.71% with Bu30 compared to n-heptane at 393 K intake temperature. Indicated mean effective pressure decreased at all intake temperatures with n-heptane. Very low amount of NOx emissions were measured with test fuels. NOx emissions were increased with the increase of intake temperature. It is also seen that CO emissions were increased with the increase of alcohol in the test fuels. Higher HC emissions were obtained especially at lower intake temperature when ethanol was used as an additive fuel. Simulations results also show that increasing the lambda lowers the in-cylinder pressure and heat release rate for all test fuels. It was observed that the combustion phase was advanced and the combustion duration was prolonged with the increase of inlet air temperature. The starting of combustion was delayed with the increase of the amount of ethanol in the test fuel. Indicated mean effective pressure was increased by around 12.6% and was acquired as 6.10 bar for D85E15 when contrasted with D70E30 at λ = 2 and at 420 K inlet air temperature with the addition of ethanol. Indicated thermal efficiency was increased by around 11.4% and was acquired as 49.17% at λ=2 with DEE when contrasted with D85E15 at that lambda. Therefore, it was seen that diethyl ether and ethanol fuel mixes remarkably affected HCCI combustion and engine performance. As a result, it was found that the HCCI operation range can be extended using higher octane number alcohols and autoignition can be controlled